1994
DOI: 10.1177/002224299405800207
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Universals: Consumers’ Use of Brand Name, Price, Physical Appearance, and Retailer Reputation as Signals of Product Quality

Abstract: Marketing universals are defined as consumer behaviors within a segment and toward a particular product category that are invariant across cultures. Using several definitions of culture and three different criteria for universality, the authors evaluate whether the use of brand, price, retailer reputation, and physical product appearance as signals of quality are marketing universals for consumer electronics products. Using a sample representing 38 nationalities, they find that there are few differences in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
434
5
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(467 citation statements)
references
References 46 publications
18
434
5
8
Order By: Relevance
“…These results are consistent with past studies that highlight the importance of reputational assets (Dawar and Parker 1994;Parasuraman et al 1985;Zajac and Westphal 1996). However, our findings contribute to past studies by providing empirical evidence that recipients distinguish between employee and firm reputations in the adoption decision.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with past studies that highlight the importance of reputational assets (Dawar and Parker 1994;Parasuraman et al 1985;Zajac and Westphal 1996). However, our findings contribute to past studies by providing empirical evidence that recipients distinguish between employee and firm reputations in the adoption decision.…”
Section: Discussionsupporting
confidence: 93%
“…Under such conditions, the information asymmetry between buyers and sellers renders ex-ante evaluations of the service quality ambiguous (Bishop and Megicks 2002). Studies have shown that when exchange transactions are characterized by high levels of information asymmetry, buyers rely on signals that provide credible proxies of quality indicators to combat adverse selection problems, which are about the likelihood of purchasing less desirable products (Dawar and Parker 1994;Li et al 2009). In particular, there is evidence that reputational assets provide credible signals of quality for firms (Dawar and Parker 1994).…”
Section: Signaling Theorymentioning
confidence: 99%
“…Entsprechend konnten verschiedene Studien zeigen, dass sich der wahrgenommene Preis-Qualitäts-Zusammenhang verstärkt, wenn die Preisinformation mit einem konsistenten Markennamen verbunden wird (z. B. Brucks /Zeithaml/Naylor, 2000;Dawar/Parker, 1994;Monroe/Krishnan, 1985). Es lässt sich somit hinsichtlich des Vertrauens in den Hersteller der Marke keine eindeutige Hypothese über die Wirkungsrichtung ableiten.…”
Section: Nicht-monetäre Kostenunclassified
“…Ähnlich wie der Preis eines Produktes, dient dabei das Land als Qualitätsindikator und entscheidendes Kaufkriterium(Dawar/Parker 1994).Aus Sicht der Unternehmen und insbesondere des Marketingmanagements stellt sich folglich die Frage, ob und unter welchen Bedingungen eine konsequente Vermarktung und Betonung des Herkunftslandes der eigenen Produkte erfolgversprechend sind. Der Beitrag legt die aus der internationalen Studie "Swissness Worldwide"(Feige et al 2008) gewonnenen Erkenntnisse hinsichtlich der weltweiten Wahrnehmung schweizerischer und deutscher Produkte und Dienstleistungen dar, zeigt detaillierte Unterschiede auf und entwirft für das Marketingmanagement schweizerischer und deutscher Unternehmen konkrete Handlungsempfehlungen für eine wirksame Verwendung von "Swissness" bzw.…”
unclassified